The Routledge companion to the work of John R. Rickford - Blake, Renée; Buchstaller, Isabelle (Routledge, 2020)
This comprehensive collection is the first full book-length volume to bring together writing focused around and inspired by the work of John Rickford and his role in sociolinguistic research over the last four decades. Featuring contributions from more than 40 leading scholars in the field, the volume integrates both historical and current perspectives on key topics in Rickford's body of work at the intersection of language and society, highlighting the influence of his work from diverse fields such as sociolinguistics, stylistics, creole studies, and language and education. The volume is organized around four sections, each representing one of the fundamental strands in Rickford's scholarship over the course of his career, bookended by short vignettes that feature stories from the field to more broadly contextualize his intellectual legacy: Language contact from a sociolinguistic and sociohistorical point of view The political ramifications of linguistic heterogeneity The stylistic implications of language variation and change The educational implications of linguistic heterogeneity and social injustice Taken together, The Routledge Companion to the Work of John R. Rickford serves as a platform to showcase Rickford's pioneering contributions to the field and, in turn, to socially reflective linguistic research more generally, making this key reading for students and researchers in sociolinguistics, creole studies, language and style, and language and education
Description based on online resource; title from digital title page (viewed on October 03, 2019)
Keywords: Sociolinguistics; Languages in contact; Language and culture; Festschrift